Изучение теплопроводности композиционных материалов на основе алмаза, кубического нитрида бора, карбида вольфрама и нитрида алюминия - Осипов, А.С.; Коростышевский, Д.Л.; Никишина, М.В.; Сербенюк, Т.Б.; Колабылина, Т.В.; Ткач, С.В.; Стратийчук, Д.А.; Фесенко, Е.И.; Часнык, В.И.; Гажа, Г.П.; Беловол, В.С.; Смирнова, Т.И.; et al. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Data on measuring the thermal conductivity coefficient of the diamond, cubic boron nitride, tungsten carbide and aluminum nitride based composites obtained by the HP-HT treatment, hot pressing and pressureless sintering are presented. The composite materials are characterized by thermal conductivity from 16 to 430 W/(m∙К) depending on the structure of matrix and inclusions. The measured vast range of thermal conductivity values of the composites can be used for improving quality and estimation of the possible fields of their application as cutting tool and wear resistant materials.